Internal Factors of Low ESP Learners’ Motivation to Speak: The Case of Cruise Staff - Athena, Tera; Kiptiyah, Mariyatul; Jannah, Faichatul (NOBEL: Journal of Literature and Language Teaching, 2023)
Cruise ship companies highly require staff to speak English fluently. Poor speaking performance of the staff members considerably impacts the company’s performance. In this era, many youths enter the realm of cruise ships. Of course, they need to deepen their learning of English from an early age before they plunge into a cruise ship field. However, the youths are not motivated to learn to speak earlier. This situation will be an obstacle that hinders the smooth actualization of educational goals, which refers to preparing individuals mentally to serve themselves and the community, especially for their careers as cruise ship staff. The main objective of this study is to find out the internal factors that cause them to have low motivation to learn to speak English since the beginning of their educational career. In this study, the researchers selected ten youths as participants. The writers analyzed the data qualitatively and explained the findings about this topic descriptively. In sum, the results of this study reveal that the internal factors of low ESP learners’ motivation to speak are low self-confidence to speak in public, nervousness, laziness, shyness to speak, and fear of making speaking mistakes.